Metal-promoted Carboxylation of Alkynes/allenes with Carbon Dioxide - Guo, Chun-Xiang; Yu, Bing; Ma, Ran; He, Liang-Nian (Current Green Chemistry, 2015)
Carbon dioxide is generally known as one of the main greenhouse gasses which have caused a series of environmental problems. On the other hand, CO2 can also be regard as an abundant, nontoxic, renewable and economical C1-synthon in organic synthesis. Chemical utilization of CO2 has attracted more and more attentions all over the world and has been studied extensively and intensely for decades. Meanwhile, acrylic acid is a valuable chemical which has been widely used in industry. From the point of sustainable development, the direct installation of CO2 into organic compounds to afford carboxylic acid derivatives is one of the most concise and promising ways for CO2 utilization. In this article, advances in the metal-promoted carboxylation reaction of alkynes and allenes with carbon dioxide are highlighted with mechanistic understanding on a molecular level.
Keywords: allene